A non-synonymous mutation in the canine Pkd1 gene is associated with autosomal dominant polycystic kidney disease in Bull Terriers. - Puya Gharahkhani (Public Library of Science (PLoS), 2011)
Polycystic Kidney Disease is an autosomal dominant disease common in some lines of Bull Terriers (BTPKD). The disease is linked to the canine orthologue of human PKD1 gene, Pkd1, located on CFA06, but no disease-associated mutation has been reported. This study sequenced genomic DNA from two Bull Terriers with BTPKD and two without the disease. A non-synonymous G>A transition mutation in exon 29 of Pkd1 was identified. A TaqMan® SNP Genotyping Assay was designed and demonstrated the heterozygous detection of the mutation in 47 Bull Terriers with BTPKD, but not in 102 Bull Terriers over one year of age and without BTPKD. This missense mutation replaces a glutamic acid residue with a lysine residue in the predicted protein, Polycystin 1. This region of Polycystin 1 is highly conserved between species, and is located in the first cytoplasmic loop of the predicted protein structure, close to the PLAT domain and the second transmembrane region. Thus, this change could alter Polycystin 1 binding or localization. Analytic programs PolyPhen 2, Align GVGD and SIFT predict this mutation to be pathogenic. Thus, BTPKD is associated with a missense mutation in Pkd1, and the application of this mutation specific assay could reduce disease transmission by allowing diagnosis of disease in young animals prior to breeding.